Analysis and improvement in the Electrical Discharge Machining process used on the manufacturing of moulds for plastics injection moulding. Issue 1 (October 2021) - Costa, A; Ferreira, L P; Silva, F J G; Sá, J C; Pereira, M T; Ávila, P
Abstract: Due to increasing competitiveness in the industry, companies will invariably adopt strategies to ensure that their employees continuously eliminate waste and create more value. This concept was applied at a company that designs, develops, and manufactures steel moulds for the injection of thermoplastics, with the purpose of implementing Lean thinking in the production sector, thus achieving the following objectives: organization of production; preparation of documents to support production, and standardization of graphite stock. Regarding the application of the 5S tool, an improvement in worker safety, and in cleaning was observed, which also led to a reduction in the time wasted when locating tools. Through the implementation of 5S auditing, enabling to verify an overall improvement, from a rating of 35% in the first audit to 85% in the subsequent audit. The tools implemented allowed for improvements in communication between sectors, leading to increased productivity and productive autonomy. Finally, graphite stock was standardized by means of Kanban .